2017
DOI: 10.1038/srep43436
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide in deep waters from the Mediterranean Sea, South Atlantic and South Pacific Oceans

Abstract: Hydrogen peroxide (H2O2) is present ubiquitously in marine surface waters where it is a reactive intermediate in the cycling of many trace elements. Photochemical processes are considered the dominant natural H2O2 source, yet cannot explain nanomolar H2O2 concentrations below the photic zone. Here, we determined the concentration of H2O2 in full depth profiles across three ocean basins (Mediterranean Sea, South Atlantic and South Pacific Oceans). To determine the accuracy of H2O2 measurements in the deep ocean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 57 publications
1
50
1
Order By: Relevance
“…Additionally, many probes show a lack of selectivity, which means they react readily (and sometimes even much faster than with H 2 O 2 ) with another analyte. Another quite problematic issue becomes apparent when looking at the published values of H 2 O 2 concentration in different samples (summarized in the Supplementary Materials [24,25,110,128,[135][136][137] is a highly important analyte and it will be important for future research to be able to quantify this analyte in real time. We think there is still room for new creative sensing schemes and solutions, but also improvements of current methods are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, many probes show a lack of selectivity, which means they react readily (and sometimes even much faster than with H 2 O 2 ) with another analyte. Another quite problematic issue becomes apparent when looking at the published values of H 2 O 2 concentration in different samples (summarized in the Supplementary Materials [24,25,110,128,[135][136][137] is a highly important analyte and it will be important for future research to be able to quantify this analyte in real time. We think there is still room for new creative sensing schemes and solutions, but also improvements of current methods are needed.…”
Section: Discussionmentioning
confidence: 99%
“…FIA analysis of H2O2 relies on a few chemiluminescent reactions, where the two most frequently used reactions in the literature are (1) acridinium ester (10-methyl-9-(p-formylphenyl)-acridinium carboxylate trifluoromethanesulfonate) [127][128][129][130][131] and (2) luminol and a Co(II) catalyst [132][133][134][135][136]. Less frequently used reactions involve (3) TCPO (bis-(2,4,6-trichlorophenyl)oxalate) [110] or (4) the oxidation of phenol [137].…”
Section: Flow Injection Analysismentioning
confidence: 99%
“…Other studies have showed that at nanomolar levels of Fe(II), H 2 O 2 and O 2 compete in the oxidation of inorganic ferrous species (González-Dávila et al, 2006). In oligotrophic ocean waters, as the ESTOC site, the levels of H 2 O 2 are generally less than 20 nM, below 200 m of depth (Hopwood et al, 2017b). With levels of H 2 O 2 < 125 nM, oxygen saturated conditions and pH > 7.5, O 2 dominates the oxidation kinetics of inorganic species of Fe(II), since the k app by O 2 is proportional to [OH − ] 2 and the k app by H 2 O 2 is proportional to [OH − ] ( Moffett and Zika, 1987;González-Dávila et al, 2006).…”
Section: The Kinetic Modeling Approachesmentioning
confidence: 98%
“…Hydrogen peroxide is more stable than superoxide in natural waters, with pseudo-firstorder decay rate constants approximately three orders of magnitude lower than that of superoxide. Consequently, H 2 O 2 has a lifetime of ∼1 to 2 d, and typical concentrations are ∼10 3 higher for H 2 O 2 than for superoxide [from <1 nM in the deep ocean to ∼100 nM in sunlight surface water (53,54)]. Typical production and decay rates range from 0.8 to 2.4 nM•h −1 for dark seawater (53) and 0.9 to 8.3 nM•h −1 in sunlit seawater (55).…”
Section: The Fate Of Superoxidementioning
confidence: 99%